2018
DOI: 10.1111/anu.12815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary conjugated linoleic acid on growth performance, tissue adipocytokine levels and lipid metabolism of grass carp

Abstract: A 65‐day growth trial was conducted to investigate the effects of dietary conjugated linoleic acid (CLA) on growth performance, tissue adipocytokine levels and lipid metabolism of grass carp. Seven isonitrogenous and isolipidic diets were formulated as follows: 0 (control), 5 (CLA5), 10 (CLA10), 15 (CLA15), 20 (CLA20), 25 (CLA25) and 30 (CLA30) g/kg CLA. Results showed that incorporating as low as 25 g/kg CLA in the diet significantly decreased the growth of grass carp. The liver lipid content in fish fed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Increased lipid peroxidation leads to formation of MDA and the content of MDA reveals the degree of the free radical attack. So, the result indicates that high levels of EHPB may cause damage to tissue, which was also confirmed by the erosion of the intestinal wall and the high levels of BUN, AST and ALT, the indicators of liver and kidney damage (Zou et al., 2018). Moreover, the low levels of complement C3 and C4 indicated that high‐EHPB diet reduced the ability of turbot to resist the invasion of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Increased lipid peroxidation leads to formation of MDA and the content of MDA reveals the degree of the free radical attack. So, the result indicates that high levels of EHPB may cause damage to tissue, which was also confirmed by the erosion of the intestinal wall and the high levels of BUN, AST and ALT, the indicators of liver and kidney damage (Zou et al., 2018). Moreover, the low levels of complement C3 and C4 indicated that high‐EHPB diet reduced the ability of turbot to resist the invasion of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 89%
“…It indicates that high-EHPB diet may cause accumulation of some toxic substances, possibly aromatic amino acid derivatives in the intestinal tract, which will cause damage to the body, lead to the disorder of intestinal microbial community, and then affect the digestion and absorption of nutrients. ALT, the indicators of liver and kidney damage (Zou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because one of the effects of CLA on lipid metabolism is to induce β-oxidation, due to increases in activity and expression of carnitine palmitoyltransferase type I (Nagao et al, 2005), this effect may have caused reductions of SFA and MUFA in A. altiparanae carcasses. Moreover, several studies have suggested that CLA can alter the expression of genes related to lipid metabolism (Yessoufou et al, 2009;Minghetti et al, 2011;Mondragón, 2016;Zou et al, 2018), especially the peroxisome proliferator activated receptors (PPARs), which act as transcription factors in various tissues such as liver, muscle, and adipose tissue (Yessoufou et al, 2009). Peroxisome proliferator-activated receptor alpha (PPARα) and gamma (PPARγ) are of great importance to the regulation of lipid metabolism (Minghetti et al, 2011), with increases in their activity being correlated with reductions in lipogenesis and increases in lipolysis through β-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing CLA levels in animals through the diet can improve the nutritional quality of their carcass. It is known that CLA levels are related to the expression of transcription factors and other genes as well as to the activity of enzymes involved in lipid metabolism (Minghetti et al, 2011;Mondragón, 2016;Zou et al, 2018) in a lowering-lipid effect. It has been indicated that CLA induces the expression of PPARγ and PPARα (Dong et al, 2014), important transcription factors for lipid metabolism regulation involved in the reduction of lipogenesis and increase on lipolysis, through β-oxidation (Minghetti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…n3 and n6 fatty acids can reduce the activity of cathepsin B and L in the muscle of Atlantic salmon ( Bahuaud et al, 2009 ). Dietary CLA can increase the level of adiponectin in the muscle of grass carp ( Zou et al, 2018 ), which is the upstream signalling molecule of TGF-β1/Smad signalling in rats ( Gao, Liu, Han, Wu, & Li, 2017 ). Therefore, CLA might affect cathepsins’ activity, collagen synthesis as well as muscle fibre growth, thereby affecting muscle hardness, which requires further study.…”
Section: Introductionmentioning
confidence: 99%